Child Education in the Household Islamic Education Management Perspective - Halimatussakdiah Halimatussakdiah (Jurnal al-Thullab, 2023)
The purpose of writing this article is to reveal the basic concepts of Islamic Education for children at the golden age (0-6 years) and reveal the concept of Management of Islamic Education for children aged 0-2 years in households. The method used is descriptive-qualitative through library research and documentary techniques which are then analyzed using the Content Analysis method. Based on the results of the study it was found that; the concept of Management of Islamic Education for early childhood in the household, includes: (1) Planning (planning) of Islamic education which refers to the theory of W5 1 H (What, who, when, where, why, and how), and is carried out in the household by the main teacher namely parents (father and mother) and family. (2) Implementation (actuating) on the basis of the Qur'an, al-Sunnah and Ijtihad), educational goals (physical, spiritual, and intellectual), educational methods (models, habituation and training, advice/reward, supervision, punishment/ penalty). (3) Evaluation (controlling) of various aspects in accordance with the goals and competency standards of Early Childhood Education that have been determined, namely: (a) moral aspects and religious values, (b) social, emotional and independence aspects, (c) language aspects, (d) cognitive aspects, (e) physical/motor aspects, and (f) artistic aspects. Tujuan penulisan artikel ini adalah untuk mengungkap konsep dasar Pendidikan Islam bagi anak pada usia keemasan (0-6 tahun) dan mengungkap konsep Manajemen Pendidikan Islam bagi anak usia 0-2 tahun di rumah tangga. Metode yang digunakan yaitu deskriptif- kualitatif melalui studi kepustakaan (library research) dan teknik dokumenter yang selanjutnya dianalisis dengan métode Content Analisis. Berdasarkan hasil penelitian diperoleh bahwa; konsep Manajemen Pendidikan islam bagi anak usia dini di rumah tangga, meliputi: (1) Perencanaan (planning) pendidikan Islam yang mengacu pada teori W5 1 H (What,who, when, where, why, and how), dan dilakukan di rumah tangga oleh guru utamanya yaitu orang tua (ayah dan ibu) serta  keluarga. (2)  Pelaksanaan (actuating) dengan dasar Al-Qur’an, al-Sunnah dan Ijtihad), tujuan pendidikan (jasmani, rohani, dan akal), metode pendidikan (teladan, pembiasaan dan latihan, nasehat/ penghargaan, pengawasan, hukuman/ sanksi). (3) Evaluasi (controlling) dari berbagai aspek sesuai dengan tujuan dan standar kompetensi Pendidikan Anak Usia Dini yang telah ditentukan, yaitu: (a) aspek moral dan nilai-nilai agama, (b) aspek sosial, emosional dan kemandirian, (c) aspek bahasa, (d) aspek kognitif, (e) aspek fisik/ motorik, dan (f) aspek seni.